Augmentation of Endogenous Acetylcholine Uptake and Cholinergic Facilitation of Hippocampal Long-Term Potentiation by Acetylcholinesterase Inhibition. (15th April 2019) - Masuoka, Takayoshi; Uwada, Junsuke; Kudo, Makiko; Yoshiki, Hatsumi; Yamashita, Yuka; Taniguchi, Takanobu; Nishio, Matomo; Ishibashi, Takaharu; Muramatsu, Ikunobu
Abstract: Hippocampal cholinergic activity enhances long-term potentiation (LTP) of synaptic transmission in intrahippocampal circuits and regulates cognitive function. We recently demonstrated intracellular distribution of functional M1-muscarinic acetylcholine receptors (mAChRs) and neuronal uptake of acetylcholine (ACh) in the central nervous system. Here we examined whether endogenous ACh acts on intracellular M1-mAChRs following its uptake and causes cholinergic facilitation of hippocampal LTP. ACh esterase (AChE) activities and [ 3 H]ACh uptake was measured in rat hippocampal segments. LTP of evoked field excitatory postsynaptic potentials at CA1 synapses was induced by high frequency stimulation in hippocampal slices. Pretreatment with diisopropylfluorophosphate (DFP) irreversibly inhibited AChE, augmented ACh uptake, and significantly enhanced the LTP. This cholinergic facilitation was inhibited by pirenzepine, a membrane-permeable M1 antagonist, while only the early stage of cholinergic facilitation was inhibited by a membrane-impermeable M1 antagonist, muscarinic toxin 7. Tetraethylammonium (TEA) inhibited ACh uptake in hippocampal segments and selectively suppressed late stage cholinergic facilitation without changing the early stage. In contrast, LTP in DFP-untreated slices was not affected by the muscarinic antagonists and TEA. Carbachol (CCh; an AChE-resistant muscarinic agonist) competed with ACh for its uptake and produced cholinergic facilitation of LTP in DFP-untreated slices. The late stage of CCh-induced facilitation was also selectively inhibited by TEA. Our results suggest that when AChE is inactivated by inhibitors, LTP in hippocampal slices is significantly enhanced by endogenous ACh and that cholinergic facilitation is caused by direct activation of cell-surface M1-mAChRs and subsequent activation of intracellular M1-mAChRs after ACh uptake. Highlights: Diisopropylfluorophosphate (DFP) irreversibly inhibited acetylcholine esterase. DFP augmented acetylcholine uptake and enhanced the LTP in the hippocampus. All stages of LTP facilitation induced by DFP were inhibited by pirenzepine. The early stage of the LTP facilitation was inhibited by muscarinic toxin 7. Tetraethylammonium suppressed the late stage of the LTP facilitation.